Bleaching of sugar cane juice using a food-grade adsorber resin and explained by a kinetic model describing the variation in time of the content of adsorbate. (April 2018) - Cruz-Tirado, JP; Cabanillas, Arnold; Siche, Raúl; Espina, J; Díaz-Sánchez, Leonardo; Ibarz, Albert
This work studies the adsorption of colored compounds in cane juice using a food-grade macroporous adsorber resin without functional groups. The adsorption equilibrium was studied through the adsorption isotherms at 30, 40, and 50 ℃. The absorbance at 420 nm was used to measure the concentration of colored compounds, which enables correlation of the residual concentration with the adsorbed concentration. Furthermore, the efficiency of the adsorption process was studied, from which it was observed that there was an improvement in efficiency with increasing resin content, while the increase in temperature was less important in the process. The kinetic study was performed using the Ibarz model and intraparticle diffusion model, which correctly account for the kinetics of the adsorption process. The adsorption kinetic constant was always greater than the desorption kinetic constant, indicating that the adsorption step predominates over the desorption step.